MICORPROPAGATION OF VIBURNUM OPULUS (ROSEUM) BY USING SINGLE NODES - Yaseen, Suaad A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was carried out to investigate  the micropropagation of viburnum opulus (Roseum) by using single nodes with axillary buds excised from soft cuttings using full strength MS salts, 30g.l-1 sucrose, 7g.l-1 Agar and different concentrations of plant growth regulators in culture medium. Results of the experiment at initiation stage revealed that the culture of single nodes of viburnum on a medium containing 4 mg.l-1 BA gave the highest number of shoots (2.21 shoots/explant). Concerning the interaction, a nutrient medium containing (2 mg.l-1 BA+ 0.4 mg.l-1 IAA) gave the highest values of mean number of shoots, leaves and length of new shoots (1.61 shoots/explant, 2.01 leaves/explant, 1.61 cm respectively). At shoot multiplication stage, the addition of 2.0 mg.l-1 from both BA and kinetin gave the highest number of shoots per explant estimated at 2.65 and 3.31 shoots/explant respectively at root formation stage; the interaction treatment of full MS salt strength with the use of 0 .5 mg.l-1 NAA gave the highest rooting percentage reaching 85.5 %. The highest number of roots (18 roots/ explant) was recorded as well from the combined treatment of full MS salt strength with the use of 0.5 mg.l-1 NAA. While the longest roots (6.65 cm) were recorded from the interaction treatment of half salt strength and 0.50 mg.l-1 IBA..